The rebranding strategy of Azarine Cosmetic - Sukamto, Valerie Phoebe; Primadini, Intan (Universitas Padjadjaran, 2023)
Background: Brands and companies become more competitive nowadays, and there is a need to maintain its existence, especially in sector such as cosmetic and beauty. Implementing a corporate rebranding process is one thing that the brand or company can do to ensure its survival. Azarine Cosmetic is a local cosmetic and beauty brand that has undergone corporate rebranding and has grown significantly. Purpose: This study aims to analyze the rebranding strategy implementation and outcomes as indicators of Azarine Cosmetic’s corporate rebranding success. Methods: This study uses a qualitative descriptive approach with a case study method. Data are collected through interviews and literature review, then analyzed with pattern matching analysis. Results: Azarine Cosmetic’s rebranding strategy was implemented based on marketing mix variables. Product, from spa products to skincare. Price, affordable based on the product size. Place, from B2B to offline and online B2C distribution. Promotion, the use of social media and other brand activation to communicate the corporate rebranding process to the external public. These implementations lead to corporate rebranding outcomes, such as sales growth of 600% in 2021; awareness and sales objectives reached, including brand image change; other supplementary achievements like awards and ease of collaborations. Conclusion: The corporate rebranding of Azarine Cosmetic was completed in five stages, including rebranding strategy implementation and outcomes. Azarine Cosmetic was implementing its rebranding strategy to the external public by updating and aligning all aspects of the marketing mix. Implications: The findings of the study can provide input for Azarine Cosmetic to strengthen the corporate rebranding outcomes, such as opening a flagship store to reflect the distinctive brand identity and conducting measurable in-depth evaluations.